Microbial Community Succession and Nutrient Changes During the Fermentation Process of Sweet Fermented Oats by Pediococcus pentosaceus - REN Fei; CHEN Shu; LIU Ming; LIU Yan-xiang; TAN Bin (Liang you shipin ke-ji)
In this study, sweet fermented oats were fermented and made by Pediococcus pentosaceus. The strain was previously isolated in the lab. Illumina sequencing was employed to analyze the succession of microbial communities and changes throughout the fermentation process. The results indicated that at the phylum level, Firmicutes displayed absolute dominance, with relative abundances increasing from 68.84% at 24 h to 69.49% at 48 h, followed by reaching a peak of 94.81% at 72 h of fermentation. At the genus level, the initial inoculant, Pediococcus, maintained a significant advantage throughout the fermentation process and peaked at 59.69% at 72 h. Principal Component Analysis (PCA) revealed the distinct clustering of the sweet fermented samples at 24 h, 48 h, and 72 h, and each exhibiting different microbial community compositions and succession patterns. The contents of lactic acid, flavonoids, amino acids, and reducing sugars showed a continuous increase from 0 to 72 h, peaking at 72 h, whereas starch content exhibited an inverse trend. The bacterial composition during fermentation was significantly correlated with the properties of the sweet fermented oats. Functional analysis of the bacterial communities using COG (Clusters of Orthologous Groups) demonstrated that primary functions were associated with RNA modification and processing, chromatin structure dynamics, energy generation and conversion, amino acid transport and metabolism, nucleotide transport and metabolism, and carbohydrate transport and metabolism. Carbohydrate transport and metabolism reached their highest abundance at 72 h. This research could provide a theoretical foundation for the development of microbial agents exploiting in fermented grain products, and promote on the research and development of whole grain fermented foods.